2004
DOI: 10.1021/nl049477p
|View full text |Cite
|
Sign up to set email alerts
|

Individually Addressable Conducting Polymer Nanowires Array

Abstract: A facile technique for fabrication of individually addressable, conducting polymer nanowire arrays of controlled dimension, high aspect ratio, and site-specific positioning using electrodeposition between electrodes in channels created on semiconducting and insulating surfaces that can be easily scaled up is reported. In addition, the ability to create “arrays” of conducting polymer nanowires of same or different materials on the same chip has been demonstrated. The fidelity, quality, and electrical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
155
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(161 citation statements)
references
References 18 publications
2
155
0
2
Order By: Relevance
“…Parallel nanowires that are separated by a nanoscale gap in the lateral dimension are useful for a number of applications, in sensing, [76,77] as electrodes for dielectrophoresis [78,79] and electrochemistry, [80] in molecular electronics, [81,82] and as a platform for interrogating phenomena that occur over the nanoscale in charge transport [35] or plasmonics. [83] There are few methods of generating such nanowire electrodes.…”
Section: Fabrication Of Addressable Nanowires Separated By a Nanogapmentioning
confidence: 99%
“…Parallel nanowires that are separated by a nanoscale gap in the lateral dimension are useful for a number of applications, in sensing, [76,77] as electrodes for dielectrophoresis [78,79] and electrochemistry, [80] in molecular electronics, [81,82] and as a platform for interrogating phenomena that occur over the nanoscale in charge transport [35] or plasmonics. [83] There are few methods of generating such nanowire electrodes.…”
Section: Fabrication Of Addressable Nanowires Separated By a Nanogapmentioning
confidence: 99%
“…Inside a microfabricated nanochannel, nanowires were engineered through monomer electrochemical polymerization, which behaves like a new electrochemical cell. Manifold nanochannels and electrochemically polymerized pyrrole/aniline production further prepares the array of ''numerous independently addressable'' nanowires of polypyrrole (PPy) and polyaniline (PANI) (Ramanathan et al 2004;Wanekaya et al 2006). In the presence of avidin conjugated with ZnSe/ CdSe quantum dots, it was found that the polymerization process of pyrrole entraps quantum dot conjugates within the nanowires (Ramanathan et al 2004).…”
Section: Indium Oxide (In 2 O 3 ) Nanowiresmentioning
confidence: 99%
“…Manifold nanochannels and electrochemically polymerized pyrrole/aniline production further prepares the array of ''numerous independently addressable'' nanowires of polypyrrole (PPy) and polyaniline (PANI) (Ramanathan et al 2004;Wanekaya et al 2006). In the presence of avidin conjugated with ZnSe/ CdSe quantum dots, it was found that the polymerization process of pyrrole entraps quantum dot conjugates within the nanowires (Ramanathan et al 2004). A template-free technique was pertained for large array-oriented electrochemical deposition of polyaniline nanowires (Liu and Ju 2003).…”
Section: Indium Oxide (In 2 O 3 ) Nanowiresmentioning
confidence: 99%
“…Since the electrical conductivity of conjugated polymers can be increased by many orders of magnitude from 10 -10 -10 -5 to 10 3 -10 5 S/cm upon doping (MacDiarmid, 2002), conducting polymer nanotubes and nanowires (e.g., polyacetylene, polyaniline (PANI), polypyrrole (PPY), and poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylenevinylene) (PPV)), are promising materials for fabricating polymeric nanodevices such as field-effect transistors (Aleshin, 2006), actuators (Jager et al, 2000), bioand chemical sensors (Huang et al, 2003;Ramanathan et al, 2004), nano light emitting diodes, electrochromic displays (Cho et al, 2005), artificial muscles, and solar cells, etc. By now, conducting polymer nanotubes and nanowires can be prepared by various methods such as the template-guided synthesis (Martin, 1994), template-free method (Wan, 1999), interfacial polymerization (Huang et al, 2003), electrospinning (MacDiarmid, 2001), dilute polymerization (Chio & Epstein, 2005), reverse emulsion polymerization method , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, focused-ion beam assisted deposition technique has been employed to attach metal microleads on isolated www.intechopen.com A Review on Electronic Transport Properties of Individual Conducting Polymer Nanotubes and Nanowires 225 nanotubes/wires directly (Long et al, 2003a(Long et al, , 2004b(Long et al, & 2005bHuang et al, 2006;Long et al, 2006c;Duvail et al, 2007;Lu et al, 2007;Long et al, 2008aLong et al, & 2009b. There are also reports demonstrating a directed electrochemical nanowire assembly technique for the fabrication and measurement of polymer nanowire arrays between pre-patterned electrodes (Ramanathan et al, 2004). All these recent investigations contribute significantly to identify and understand the specific electrical behaviour of conjugated polymer nanwires and nanotubes in comparison to the bulk materials.…”
Section: Introductionmentioning
confidence: 99%